PENINGKATAN HASIL BELAJAR MEKANIKA TEKNIK MELALUI PENERAPAN PEMBELAJARAN KOOPERATIF TIPE TAI (TEAM ASSISTED INDIVIDUALIZATION) PADA SISWA KELAS X TGB B SMK NEGERI 2 SUKOHARJO TAHUN PELAJARAN 2014/2015 - Jaka Rahmana; Agus Efendi; Abdul Haris Setiawan (Indonesian Journal Of Civil Engineering Education, 2015)
The purpose of this research is to improve gacor5000 the teaching of engineering mechanics and explain the mechanism of implementation of engineering mechanics of learning through the implementation of cooperative learning TAI (Team Assisted Individualization) in class X SMK TGB B 2 Sukoharjo academic year 2014/2015.This study uses a Class Action Research (CAR). This study was conducted in two cycles, with each cycle consisting of planning, action, observation, and reflection. The subjects in this study TGB B class X SMK Negeri 2 Sukoharjo the school year 2014/2015 amounted to 32 consist of 17 boys and 15 girls. Data collection techniques with learning outcomes assessment calculations simple construction, observation, and interviews. The data analysis technique used in this research is descriptive qualitative analysis based on the percentage.Based on data analysis results: The implementation of cooperative learning TAI (Team Assisted Individualization) can improve the mechanics of learning techniques in class X TGB B SMK Negeri 2 Sukoharjo. It can be seen from the results of research. Student learning outcomes cognitive domains (Pre Cycle of 31.25%; the first cycle was 65.63%; Cycle II amounted to 90.63%). Affective student learning outcomes (Pre cycle of 53.02%; the first cycle was 64.06%; Cycle II amounted to 78.23%). Psychomotor student learning outcomes (Pre cycle of 43.19%; the first cycle was 62.50%; Cycle II amounted to 80.08%). Teacher performance assessment scores in learning activities (Pre cycle of 34.40%; the first cycle was 69.79%; Cycle II amounted to 90.625%).Based on the research that has been conducted conclusion of this research is the application of learning models TAI (Team Assisted Individualization) can improve the mechanics of learning techniques in class X TGB B SMK Negeri 2 Sukoharjo the school year 2014/2015. Keywords: Team Assisted Individualization, (TAI), learning outcomes, Engineering Mechanics